1992
DOI: 10.1159/000213319
|View full text |Cite
|
Sign up to set email alerts
|

Age Stability of Human Brain 5-HT Terminals Studied with [<sup>3</sup>H]Paroxetine Binding

Abstract: The effect of age on serotonin uptake sites labeled with [3H]pa-roxetine was studied in two sets of brains. The first set included 28 subjects (19 males and 9 females) between the ages 0 and 100 years. The cortex of cingulate gyrus and the amygdala were studied. No age-related changes in binding capacity (Bmax) or binding affinity (Kd) were noted. In the second set, the frontal cortex and hypothalamus from 22 subjects (18 males and 4 females) between 16 and 75 years were studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 10 publications
3
7
1
Order By: Relevance
“…The reported results, together with previous findings of unchanged number of cortical 5-HT nerve terminals, as indirectly measured through the [3H]paroxetine binding to the 5-HT uptake sites (Andersson et al, 1992;Arranz et al, 1993), might indicate that changes with age in the rate of synthesis, degradation, or in the membrane lipid composition of the 5-HT receptors might account for the reductions in the number of cortical 5-HT1D and 5-HT2 binding sites found in the same brain material (Arranz et al, 1993).…”
Section: The Serotonergic Systemsupporting
confidence: 84%
“…The reported results, together with previous findings of unchanged number of cortical 5-HT nerve terminals, as indirectly measured through the [3H]paroxetine binding to the 5-HT uptake sites (Andersson et al, 1992;Arranz et al, 1993), might indicate that changes with age in the rate of synthesis, degradation, or in the membrane lipid composition of the 5-HT receptors might account for the reductions in the number of cortical 5-HT1D and 5-HT2 binding sites found in the same brain material (Arranz et al, 1993).…”
Section: The Serotonergic Systemsupporting
confidence: 84%
“…Importantly, as in a previous study (Andersson et al, 1992), no relationship could be found in this study between either the affinity or the density of [3H]paroxetine binding with the age of the donor or the PMI for the tissue. As [3H]paroxetine is a highly selective ligand for the serotonin transporter (Habert et al, 1985;Mellerup et al, 1986;Marcusson et al, 1988), these data indicate that the serotonin transporter is a stable molecule which is suitable for study using autopsy tissue.…”
Section: Discussioncontrasting
confidence: 48%
“…These findings show concordancy upon the different brain regions studied, and are in agreement with data reported by other researchers (Lawrence et al, 1990;Andersson et al, 1992) who did not find any significant differences in human brains from suicide victims. Similar results with respect to age-related changes have been reported for both [3H]imipramine and [3H]paroxetine binding sites, which may indicate the stability of the 5-HT terminals with increasing age in the human brain (Andersson and Marcusson, 1990;Andersson et al, 1992).…”
Section: Discussionsupporting
confidence: 93%